Students’ perceptions of need-supportive teaching, basic psychological need satisfaction, and life skills development in Chinese physical education - Xiangbo Ji; Shaofeng Zheng; Liping Cheng (Frontiers in Psychology)
IntroductionPhysical education (PE) is viewed as an environment conducive to students’ life skills development. However, less is known about the processes by which young people develop their life skills in PE. This is particularly the case in non-English speaking countries such as China. Based on self-determination theory, the present study aimed to investigate the relationships between students’ perceptions of teacher need-support, basic psychological need satisfaction and their life skills development in PE.MethodsThe present study employed a cross-sectional design. Participants were 727 Chinese students (Mage = 16.93) attending 29 classes from 7 different schools in China. They completed measures assessing these variables. The preliminary analyses used descriptive statistics to determine participants’ scores on each variable and correlations to assess the relationship between variables. Mediation analyses were conducted to evaluate the tested models.ResultsIn all analyses, structure, autonomy support, involvement, and total teacher need-support was positively correlated with total psychological need-satisfaction, which, in turn, positively correlated with students’ life skills development in PE. The mediation analyses showed that total psychological need-satisfaction was a key mediator between teacher need-support and students’ life skills development in PE.ConclusionThis study thus provides actionable insights into the role that teacher need-support plays in satisfying students’ basic psychological needs and, in turn, developing students’ life skills in PE. The findings highlight that teachers should exhibit need-support (e.g., provide students with constructive, clear, and self-oriented feedback; identify students’ interests, preferences and acknowledge their opinions; and develop an effective bond with students) in order to satisfy students’ three basic psychological needs and promote their life skills development in PE.